AmcA—a putative mitochondrial ornithine transporter supporting fungal siderophore biosynthesis - Schafferer, Lukas; Beckmann, Nicola; Binder, Ulrike; Brosch, Gerald; Haas, Hubertus (Frontiers in Microbiology, 2015)
Iron is an essential nutrient required for a wide range of cellular processes. The opportunistic fungal pathogen Aspergillus fumigatus employs low-molecular mass iron-specific chelators, termed siderophores, for uptake, storage and intracellular iron distribution, which play a crucial role in the pathogenicity of this fungus. Siderophore biosynthesis depends on coordination with the supply of its precursor ornithine, produced mitochondrially from glutamate or cytosolically via hydrolysis of arginine. In this study, we demonstrate a role of the putative mitochondrial transporter AmcA (AFUA_8G02760) in siderophore biosynthesis of A. fumigatus. Consistent with a role in cellular ornithine handling, AmcA-deficiency resulted in decreased cellular ornithine and arginine contents as well as decreased siderophore production on medium containing glutamine as the sole nitrogen source. In support, arginine and ornithine as nitrogen sources did not impact siderophore biosynthesis due to cytosolic ornithine availability. As revealed by Northern blot analysis, transcript levels of siderophore biosynthetic genes were unresponsive to the cellular ornithine level. In contrast to siderophore production, AmcA deficiency did only mildly decrease the cellular polyamine content, demonstrating cellular prioritization of ornithine use. Nevertheless, AmcA-deficiency increased the susceptibility of A. fumigatus to the polyamine biosynthesis inhibitor eflornithine, most likely due to the decreased ornithine pool. AmcA-deficiency decreased the growth rate particularly on ornithine as the sole nitrogen source during iron starvation and sufficiency, indicating an additional role in the metabolism and fitness of A. fumigatus, possibly in mitochondrial ornithine import. In the Galleria mellonella infection model, AmcA-deficiency did not affect virulence of A. fumigatus, most likely due to the residual siderophore production and arginine availability in this host niche.